Morphological Study And Biodegradability Of Poly Lactic Acid (Pla)/ Polybutylene Adipate Terephthalate (Pbat) Reinforced With Microcrystalline Cellulose - Tharani Radha Krishnan (2021)
In recent times, awareness on plastic pollution had increase which brings innovation on new productions to be environmental friendly. Various polymers are been used in studies to analyse the suitability to produce thin films. In this study, Poly lactic acid (PLA) and Polybutylene adipate terephthalate (PBAT) was reinforced with microcrystalline cellulose (MCC) and the surface morphology and biodegradability of the thin film were studied. Characteristics of commercial microcrystalline cellulose (C-MCC) and bamboo microcrystalline cellulose (B-MCC) was analysed through Fourier Transform infrared spectroscopy (FTIR) and Brunauer-Emmett-Teller (BET) analysis to study the comparative in order to examine the properties differences. The B-MCC produced in this study proposes better surface area reading compare to the C-MCC where the reading of B-MCC is 0.019 mug while C-MCC is 0.015 m2/g. The properties of degradability of the films were tested through soil burial and the surface morphology before and after the burial were compared to analyse the differences between C-MCC and B-MCC. C-MCC and B-MCC were blended with polymers at different weight ratio (1%, 3% and 5%) with three different thicknesses (0.4mm, 0.6mm and 0.8mm) tc compare the effectiveness on the degradability of the composites while the constan, blend of this study is the PLA/PBAT composite. Morphological study on the thin fib were carried through Scanning electron micrographs (SEM), Light microscopy (LM and Atomic force microscope (AFM) to observe the dispersion of MCC, surfac' roughness and topography. Biodegradability test was carried by soil burial for 48 day spam in which at the end of analysis 5% of both microcrystalline cellulose composite recorded high percentage of weight loss. 5% of C-MCC recorded a high weight loss c 27.36% at the thickness of 0.8 while 5% of B-MCC observed to have large degradatio of 21.59% at 0.4mm thickness. However, in future studies can take forward wit different parameter and further detailed analysis to improve the properties of the blend Keywords: Poly lactic acid (PLA), Polybutylene adipate terephthalate (PBA1 Commercial microcrystalline cellulose (C-MCC), Bamboo microcrystalline cellulo (B-MCC), Biodegradability